Near-death experience in ancient civilizations: the origins of the world's afterlife beliefs - Shushan, Gregory (A sacred planet book, 2025)
"A cross-cultural comparison of ancient beliefs about death and the afterlife. Reveals the powerful influence of near-death experiences (NDEs) on the formation of religious beliefs, mystical literature, and ritual practices. Focuses on the afterlife beliefs of five ancient world regions: Old and Middle Kingdom Egypt, Sumer and Old Babylonian Mesopotamia, Vedic India, pre-Buddhist China, and Maya and Aztec Mesoamerica. Shows how the similarities among afterlife beliefs and their correspondences with NDEs reveal that they both stem from universal truths"--